Substitution of Ethynyl-Thiophene Chromophores on Ruthenium Sensitizers: Influence on Thermal and Photovoltaic Performance of Dye-Sensitized Solar Cells. (6th February 2012) - Chandrasekharam, Malapaka; Rajkumar, Ganugula; Suresh, Thogiti; Reddy, Paidi Yella
Abstract : A new high molar extinction coefficient ruthenium(II) bipyridyl complex, "Ru(2, 2-bipyridine-4, 4 ′ -dicarboxylic acid)(4, 4 ′ -bis((3-hexylthiophen-2-yl)ethynyl)-2, 2 ′ -bipyridine)(NCS)2 (N(C4 H9 )4 ), MC 101" was synthesized and fully characterized by 1 H-NMR, ESI-MASS, FT-IR, UV-Vis., and fluorescence spectroscopes. The dye showed relatively high molar extinction coefficient of 25.0 × 10 3 M -1 cm -1 at λ maximum of 544 nm, while the reference C 101 has shown 15.8 × 10 3 M -1 cm -1 at λ maximum 528 nm. The monochromatic incident photon-to-collected electron conversion efficiency of 44.1% was obtained for MC 101 over the entire visible range, while the C 101 sensitized solar cell fabricated and evaluated under identical conditions exhibited 40.1%. The DSSCs fabricated with 0.54 cm 2 active area TiO2 electrodes and high efficient electrolyte (E 01), from the sensitizers MC 101 and C 101 exhibited energy conversion efficiencies of 3.25% (short-circuit current density (J S C ) = 7.32 mA/cm 2, V O C = 610 mV, ff = 0.725) and 2.94% (J S C = 6.60 mA/cm 2 ; V O C = 630 mV; ff = 0.709), respectively, under air mass of 1.5 sunlight.